2019
DOI: 10.3390/antiox8100441
|View full text |Cite
|
Sign up to set email alerts
|

Protein Oxidation Biomarkers and Myeloperoxidase Activation in Cerebrospinal Fluid in Childhood Bacterial Meningitis

Abstract: The immunological response in bacterial meningitis (BM) causes the formation of reactive oxygen and nitrogen species (ROS, RNS) and activates myeloperoxidase (MPO), an inflammatory enzyme. Thus, structural oxidative and nitrosative damage to proteins and DNA occurs. We aimed to asses these events in the cerebrospinal fluid (CSF) of pediatric BM patients. Phenylalanine (Phe), para-tyrosine (p-Tyr), nucleoside 2′-deoxiguanosine (2dG), and biomarkers of ROS/RNS-induced protein and DNA oxidation: ortho-tyrosine (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Each with their advantages and disadvantages is described by Winterbourn and Kettle (2000). Based on the analyses of CSF collected from 79 confirmed pediatric BM cases, Rugemalira et al (2019) indicated that elevated ratios of 3Cl-Tyr:para-tyrosine serves as a marker for MPO activation in CSF in pediatric BM cases, and potentially also for grading the severity of neuroinflammation. Furthermore, Rugemalira et al (2019) also proved that 3NO 2 -Tyr can be used as a biomarker for peroxynitrite formation and is associated with an unfavorable outcome of BM.…”
Section: Myeloperoxidasementioning
confidence: 99%
See 1 more Smart Citation
“…Each with their advantages and disadvantages is described by Winterbourn and Kettle (2000). Based on the analyses of CSF collected from 79 confirmed pediatric BM cases, Rugemalira et al (2019) indicated that elevated ratios of 3Cl-Tyr:para-tyrosine serves as a marker for MPO activation in CSF in pediatric BM cases, and potentially also for grading the severity of neuroinflammation. Furthermore, Rugemalira et al (2019) also proved that 3NO 2 -Tyr can be used as a biomarker for peroxynitrite formation and is associated with an unfavorable outcome of BM.…”
Section: Myeloperoxidasementioning
confidence: 99%
“…Based on the analyses of CSF collected from 79 confirmed pediatric BM cases, Rugemalira et al (2019) indicated that elevated ratios of 3Cl-Tyr:para-tyrosine serves as a marker for MPO activation in CSF in pediatric BM cases, and potentially also for grading the severity of neuroinflammation. Furthermore, Rugemalira et al (2019) also proved that 3NO 2 -Tyr can be used as a biomarker for peroxynitrite formation and is associated with an unfavorable outcome of BM. In a study of 59 children with confirmed BM (Mirić et al, 2010), CSF MPO activity, although relatively low, was significantly increased at baseline compared to controls (n = 23), increasing even further by day 5 of treatment.…”
Section: Myeloperoxidasementioning
confidence: 99%
“…The interaction between PRRs and PAMPs trigger the activation of the oxidative burst during phagocytosis, which is initially characterized by the activity of NADPH oxidases (NOX) that generate the superoxide anion (O2 − ). This free radical could be dismuted to hydrogen peroxide (H2O2) spontaneously, but superoxide dismutases do this more efficiently ( Figure 1B) [8,10,17]. The presence of NOX proteins is critical for the control of infections.…”
Section: Molecular Pathways Of Rons-biosynthesis In Immune Cellsmentioning
confidence: 99%
“…spontaneously, but superoxide dismutases do this more efficiently ( Figure 1B) [8,10,17]. The presence of NOX proteins is critical for the control of infections.…”
Section: Molecular Pathways Of Rons-biosynthesis In Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation